PEMANFAATAN LIMBAH BUDIDAYA IKAN LELE UNTUK BUDIDAYA IKAN NILA DENGAN PADAT TEBAR BERBEDA YANG DIPELIHARA DENGAN WADAH BERTINGKAT DALAM KOLAM - rizal firdaus (Universitas Sriwijaya, 2015)
ABSTRACT The aim of this research was to determine the growth, survival of catfish (Clarias sp.) and tilapia (Oreochromis niloticus) in cage level in pond system. The research held in Laboratorium Budidaya Perairan, Aquaculture Study Program, Agriculture Faculty, Sriwijaya University on June 2015. Research used Completely Randomized Design (CRD) which areÂ three treatments and three replications, there were stocking density of catfish100 ind.m-2(166 ind.m-3) and tilapia 25 ind.m-2 (31 ind.m-3), stocking density of catfish 100 ind.m-2(166 ind.m-3) and tilapiaÂ 50 ind.m-2 (62 ind.m-3), and stocking density of catfish100 ind.m-2(166 ind.m-3) and tilapia 75 ind.m-2 (93 ind.m-3). Parameters were growth, survival and water chemical physics.The result showed that tilapia stocking density of 75 ind.m2 could balance growth and survival of catfish and tilapia that reared in leveling media in pond. Treatment of P3 with tilapia stocking density of 75 ind.m2 showed both absolute length and weight were 1.54 cm and 3.91 g, and both absolute length and weight growth of catfish were 5.91 cm, and 18.95 g. Survival rate of tilapia and catfish both were 76% and 94%. Â Keyword : Aquaculture waste, Cage, Pond, Stocking density, Catfish and Tilapia